Recording and Reporting Information System for Maternal Health Monitoring (Literature Review) - Ghinanissa Azzahra Dustar; Sri Achadi Nugraheni; Cahya Tri Purnami (International Journal of Integrative Sciences, 2023)
The Maternal and Child Health (MCH) program is a health program in Indonesia that aims to improve the health and welfare of mothers and children as stated in Permenkes number 4 of 2019. To support the implementation of the program requires technology in the form of information systems. Information systems are designed to help health workers manage maternal and child health more effectively. Delays in data collection, incomplete filling and long time in presenting data are one of the reasons why a maternal health information system is needed to run optimally. The purpose of this study was to describe the recording and reporting of maternal health monitoring activities. The method used is a literature review based on the PRISMA flow. The results of the health information system research are able to provide the right, accurate and up-to-date quality of information data so as to improve the efficiency and effectiveness of services and facilitate evaluation and help health workers manage maternal health more effectively. The running of an information system will depend heavily on human resources to utilize the information system and produce records and reports to improve the performance of users of the system